Evaluation of Genetic Diversity of Naked Neck and Frizzle Genotypes Based on Microsatellite Markers - Abou-Emera , O.K.; Ali, U.; Galal, A.; El-Safty, S.; Abdel-Hameid, E.F.; Fathi, M.M. (International Journal of Poultry Science, 2017)
Background and Objective: The identification of genetic diversity for heat resistance genotypes, such as naked neck (Na) and frizzle (F) genes, is of great interest for scientists to be discovered along with the native breeds genetic map recognition. Since they represent the most important genotype flocks raised in tropical and semi-tropical areas. The extent of feather (or plumage distribution) and feather shape (straight or curled) divergence between both genotypes (whether homozygous or heterozygous state) morphologically, comparing with normally feather flock, need to be clarified using microsatellite markers technique side by side with productive performance. Methodology: According to morphological appearance of feather coverage, a total number of 326 birds, representing 5 genotypes (homozygous naked neck (NaNa), heterozygous naked neck (Nana), homozygous frizzle (FF), heterozygous frizzle (Ff) and normally feathered (nanaff) genotypes) were classified. At sexual maturity, the chickens were individually housed in wire cages located in semi-closed house. Adult body weight, age at sexual maturity, egg number and egg weight were recorded for each genotype throughout the first six month of laying cycle. At 30 weeks of age, egg quality characteristics were examined. Forty birds were randomly assigned (8 birds/genotype) to assess cell mediated immunity through PHA-P injection in wattles. Blood samples were collected from the wing vein. The DNA was purified by successive extraction with phenol:chloroform:isoamyl alcohol (25:24:1) and chloroform:isoamyl alcohol (24:1), respectively. A total of 20 microsatellite markers were selected based on the degree of polymorphism reported in the literature. The PCR amplification was carried out in 25 μL reaction volumes, gels were stained in ethidium bromide and DNA bands were visualized on UV-transilluminator. Data of SSR analyses were scored on the basis of the presence or absence of the amplified products for each primer. The similarity coefficients were then used to construct a dendrogram by Unweighted Pair-Group Method with Arithmetical Average (UPGMA). Results: The productive results revealed that the introducing Na and F genes in chicken breeds raised under hot weather significantly improved most of egg production and eggshell quality traits. Moreover, significantly higher cell mediated response was found in naked neck and frizzle genotypes particularly, in homozygous manner compared to normally feathered genotype. The results revealed that the microsatellite markers had 83 alleles with an average of 4.2±0.24 alleles per locus. It could be observed that polymorphism ranged from 25-100% with an average of 64.7% for all markers. A remarkable extensive genetic diversity was seen among the studied genotypes. Genetic distance as a pair-wise comparison of different genotype ranged from 0.14 (NaNa-Nana) to 0.41 (Nana-FF). Both naked neck genotypes and frizzle sibs located in a separate sub-cluster resulted in a clear distinction between the two major genes. Conclusion: It was concluded that the evaluation of genetic diversity among chicken genotypes carrying Na or F based on the studied microsatellite markers was efficient and gained consistent results.